HUBUNGAN ANTARA ISLAM DAN SPIRITUALISME JAWA - Fatakhul Huda (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
Abstract Islam and Javanese spiritualism discuss the syncretic relationship between the two. This theme was raised because at present there are many who think that the teachings of Javanese spiritualism are not in accordance with the teachings of Islam. One of the reasons is the perception of the public who see that the teachings of spiritualism are thick with mystical teachings, superstitions, bid'ah, and so on. In fact, the teachings of Javanese spiritualism already existed and were taught at the same time as the arrival of Islam brought by Wali Songo. The da'wah strategy carried out by Wali Songo through culture has made Islam develop so rapidly and massively. In essence, Wali Songo did not change the entire Javanese cultural tradition, teachings that were in accordance with Islamic values ​​were maintained. Meanwhile, cultural traditions that are inconsistent with Islamic teachings are eliminated or replaced with Islamic values Appropriate theories and approaches are needed to find out more about Islam and Javanese spiritualism. The theory considered appropriate is to use perennial philosophy (philosophy of eternity), namely a view that every religion has a single and universal truth which forms the basis of all knowledge and religious doctrines or spiritualism. The concept of spiritualism is the culmination of a deep understanding of religion. The results of spiritualism give birth to attitudes of wisdom and justice in addressing problems and crises such as moral crises, harmony crises, environmental crises and so on.